PENGARUH JENIS SUMBER NITROGEN TERHADAP KARAKTERISTIK NATA DE SAGO - Heni - Mutmainnah; Farida Renhoat (Fakultas MIPA UNM, 2022)
Nata is a biotechnology product that utilizes Acetobacter xylinum in the fermentation process. Making nata requires materials that contain carbohydrates and nitrogen. The raw materials for making nata generally use coconut water, fruit extracts, and sago waste. Sago liquid waste can be used because it contains starch as a carbon source to form polysaccharides. In addition to starch content, making nata also requires nitrogen supply. Increased nitrogen supply can increase the amount of polysaccharide formed. This study aims to determine the effect of giving different types of nitrogen sources, namely urea, ZA, and touge extract and control without the addition of nitrogen on the characteristics of nata de sago. This study used the RAL method (Completely Randomized Design) which consisted of 4 treatments and 3 repetitions. The results showed that the addition of 1.5 g of urea produced the best nata characteristics based on thickness, color, and aroma, but based on texture characteristics the best value was obtained in the bean sprout extract treatment. The results of this study become an alternative to the use of sago leachate as a raw material for making nata and an alternative to the use of natural nitrogen sources from bean sprout extract which is organic and has no residue in the final product of nata.Key words: Nata de sago, nitrogen, organoleptic